Drop Everything and Read (DEAR) Activity as a Means of Increasing Students’ Reading Habits - Prasetyaningrum, Dian Islami; Ruminar, Hafida (JET ADI BUANA, 2020)
Positioned at the bottom two for the literacy level globally, Indonesia gacorqq needs to find a breakthrough to boost people’s reading habits. Reading is a complex process on how readers embracing the written text as a communication media, interpreting the text using the prior knowledge, then finally re-communicate the content as the prove of comprehension. Many students thought that reading was not enjoyable, so the concept of reading for gacorqq pleasure could help. This present study conducted to show how the Drop Everything and Read (DEAR) approach was helpful to boost the students' habits in reading with pleasure. Many previous studies conducted on several levels of education for instance primary and secondary. So, in this study, the participants were university students who joined gacorqq English for Specific Purposes (ESP) class. DEAR only needed to be implemented only for 30 minutes regularly, and then the students find out that the approach was helpful to ease their burden in reading. Moreover, the reading for pleasure concept offered in the approach implementation surely makes the students feel the joy of reading that mostly forgotten.